قاعدة: الأصل في الأشياء الإباحة وتطبيقاتها المعاصر - سحنون, طارق (University of Eloued-جامعة الوادي, 2021)
- فإن دراسة القواعد الفقهية من حيث مقوماتها، وأركانها وشروطها، وماله صلة بذلك، يعد من الأمور الهامة في مجال الفقه الإسلامي، إذ هي تمثل الوجه الثاني من أصول الفقه، ومن القواعد الفقهية المهمة التي سأدرسها في هذا البحث قاعدة: "الأصل في الأشياء الإباحة" .- The study of jurisprudence rules in terms of their components, pillars and conditions, and what is related to that, is one of the important matters in the field of Islamic jurisprudence, as it represents the second aspect of the principles of jurisprudence, and one of the important jurisprudential rules that I will study in this research is the rule: “The origin in things is permissibility.” ".
مذكرة ماستر
Keywords: قاعدة الأصل - الأشياء الإباحة - تطبيقات المعاصر; The rule of origin - Permissible things - contemporary applications